The Burden of Proving Burnout in Academic Library Workers - Johnson, Matthew; Page, Sylvia (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire)

(untitled) (Canadian Association of Professional Academic Librarians / Association Canadienne des Bibliothécaires en Enseignement Supérieur, 2024)
Current paradigms of assessment, measurement, and evidence-based practice in libraries, which inform administrative and managerial action (or inaction), construct an undue burden of proof for burnout (and other negative workplace conditions) that denies library workers the care and interventions necessary for them to thrive in their workplace and that leads to continued exploitative practices and emotional extraction.Frequently, burnout has to be proven through quantitative rather than qualitative processes, and the lack of quantitative data allows administrators to ignore burnout’s prevalence. Similarly, when solutions to burnout are considered, they're approached without consideration of individual worker needs. Through the focus on quantification, we bureaucratically obscure the individual in favour of a plurality, and develop solutions that serve those at the centre but not the margins.The phenomenon of burnout can be understood as a symptom of larger labour concerns throughout libraries and other workplaces that result from an overreliance on (quantitative) evidence-based paradigms and the mining of affect in service of “workplace wellbeing.” Library innovation, then, improves the functioning of the library for users in a model where the library is not a workplace and the library workers are not considered a user group. In some cases, library resources receive far more consideration and care than the people working in the library both in terms of space and support.